Ceria‐Supported Gold Nanoparticles as a Superior Catalyst for Nitrous Oxide Production via Ammonia Oxidation. Issue 19 (23rd February 2022) - Tang, Zhenchen; Surin, Ivan; Rasmussen, Asbjörn; Krumeich, Frank; Kondratenko, Evgenii V.; Kondratenko, Vita A.; Pérez‐Ramírez, Javier
Abstract: The production of nitrous oxide, N2 O, via NH3 oxidation is not on a practical scale due to the lack of a suitable catalyst. Instead, it is produced via thermal decomposition of NH4 NO3, rendering N2 O too costly and limiting its prospective uses. Herein, we report CeO2 ‐supported Au nanoparticles (2–3 nm) as a highly selective catalyst for low‐temperature NH3 oxidation to N2 O, exhibiting two orders of magnitude higher space–time yield than the state‐of‐the‐art Mn−Bi/α‐Al2 O3 and remarkable stability over 70 h on stream. The reaction proceeds via a Mars–van Krevelen mechanism, with the density of interfacial Au δ+ species and the oxygen storage capacity of CeO2 identified as the key performance descriptors. The latter could be enhanced by cobalt doping, improving the catalytic activity and setting a new benchmark for N2 O productivity. These findings establish NH3 oxidation as an efficient process for N2 O manufacture and facilitate its broader utilization in selective oxidations. Abstract : Ceria‐supported gold nanoparticles (2–3 nm) are highly active and selective for N2 O production via NH3 oxidation, exhibiting superior stability and two orders of magnitude higher productivity than the state‐of‐the‐art system. The interplay between interfacial Au δ+ species and active oxygen species supplied by ceria is key to the unprecedented performance.